Water quality in disturbed and undisturbed sites in Asap, Belaga - Grace, Stephen (Universiti Malaysia Sarawak, UNIMAS, 2010)
A study on water quality was carried at eight selected stations in disturbed and undisturbed sites in Asap, Belaga in three types of land uses; newly developed oil palm plantation, existing 7-year old oil palm plantation and 20-year logged-over-forest. The objective of the study is to determine water quality in disturbed and undisturbed sites in Asap, Belaga. Data such as pH, dissolved oxygen and temperature was recorded in-situ whereas nutrients, biological oxygen demand, total suspended solids and chlorophyll a were analyzed at the laboratory. The result showed the degradation of water quality which had been affected by the activity of oil palm plantation. Among all of the parameters, total suspended solids, temperature and phosphorus shows the highest value but low in dissolved oxygen in the newly developed oil palm plantation area (MPOB) compared to the other types of land uses. High total suspended solids in the water shows that the activity of land clearing affected the water quality of disturbed sites.